A new model of Master of Philosophy in physiological sciences - Ahmad, H. R.; Arain, F. M.; Khan, Naveed Ahmed * (Professional Medical Publications, 2016)
The objectives of Master of Philosophy (MPhil) in Physiological Sciences are: 1) to describe the new ways in which anatomy, biochemistry and physiology on one hand, and microbiology, pathology and pharmacology on other hand meet their functional requirements through multidisciplinary integrated concepts; 2) to elucidate relationships between cell biology, molecular biology and molecular genetics by connecting dots of how cell functions are driven by molecules and being controlled by genes. This forms the basis of cell, molecular and genetics [CMG] module upon which 7 multidisciplinary modules of Physiological Sciences follow; 3) these 24 credit hours provide the physiological basis for PhD studies as well as faculty development to enhance learning abilities of medical student; 4) the modules constitute Cardio- Respiratory Physiological Sciences, GI and Renal Physiological Sciences, Neurosciences, Endo-Reproductive Physiological Sciences.; 5) it has integrated microbiology, pathology and pharmacology in a unique way through CMG of microbes leading to associated pathology and mechanisms of prescribed drugs; 6) it has additional synopsis and thesis friendly course work leading to comprehensive examinations; 7) the year two deals with research work of 6 credit hours leading to defense of thesis; 8) The MPhil in Physiological Sciences is fundamentally different from what is being offered elsewhere. It prepares and offers a good spring board to dovetail PhD studies as well as faculty and institutional development. This is the first study that deals with innovative programmes in research, learning and education in the field of physiological sciences. This broad-based MPhil would make its recipients competent, critical, confident and productive learner. This is a completely unique design of a curriculum that has no comparable examples elsewhere. Our mission is to educate graduate students in the field of Physiological Sciences such that they have a complete grasp over the broad-based integrated concepts of basic health sciences. Upon completion of their education, the students will be able to use the duality of imagination and skepticism. Hence, the students will contribute to their fields by unfolding their creative energy.